Ill-posed internal boundary value problems for the biharmonic equation - Atakhodzhaev, M. A. (Mukarram Atakhodzhaevich) (VSP, 2002)
The Inverse and Ill-Posed Problems Series is a series of monographs publishing postgraduate level information on inverse and ill-posed problems for an international readership of professional scientists and researchers. The series aims to publish works which involve both theory and applications in, e.g., physics, medicine, geophysics, acoustics, electrodynamics, tomography, and ecology.